Complete mitochondrial genome and the phylogenetic position of the stellate puffer (Arothron stellatus). Issue 2 (3rd July 2019) - Chen, Wei-Feng; Peng, Xin; Yu, Yue; Yang, Can-Min; Chen, Xiao; Zhao, Jun; Wang, Junjie
Abstract: The complete mitochondrial genome of the stellate puffer ( Arothron stellatus ) was first determined in this study. It was a 16, 475 bp circular molecule and consisted of 37 genes with typical gene order in vertebrate mitogenome. Its nucleotide content was 29.0% A, 32.0% C, 15.9% G and 23.1% T. This mitogenome had 30 bp short intergenic spaces located in 12 gene junctions and 28 bp overlaps located in 7 gene junctions. In the protein-coding genes, two start codons (GTG and ATG) and two stop codons (TAG and TAA/TA/T) were found. The 22 tRNA genes ranged from 64 bp (tRNA- Cys ) to 74 bp (tRNA- Leu1 and tRNA- Lys ). The phylogenetic result showed that Takifugu xanthopterus was most closely related to the reef-related A. stellatus among all Tetraodontiformes species.